Assessment of the Financial Stability of Airlines with Different Business Models before, during and after the COVID-19 Pandemic - O. V. Savchina; D. A. Pavlinov (Финансы: теория и практика)
The Russian airline market for the first time since the sharp decline in passenger traffic in 2020 showed growth rates of revenue per passenger-kilometre in 2021. This indicates a step towards recovery after the biggest crisis the industry has seen in all of history. The purpose of the study is to assess the financial stability of the Russian air carriers for the last three years: 2019 (pre-COVID-19), 2020 (COVID-19) and 2021 (post-COVID-19), with the help of applying bankruptcy likelihood prediction models. The analysis was conducted for 4 airlines, each of them having a different business model that they follow (national flag carrier, low-cost carrier, ultra-low-cost carrier and regional carrier). The market positions of each airline were identified, highlighting the rapid growth of low-cost carriers, even during the COVID-19 crisis. The same cannot be said for full-service airlines, which have fallen the most in both profit and traffic. Calculations of bankruptcy models showed that low-cost airlines were more financially stable during the COVID-19 pandemic, while full-service air carriers experienced uncertainty during 2020 and only gradually recovered in 2021. These results coincide with other research regarding which business model is less vulnerable during crises, however this is very dependent on the region in which airlines operate in: both low-cost carriers and full-services airlines, according to other authors, show high financial sustainability. Such contradiction in the current research highlights the relevance of further analysis in this area to provide answers that are more concrete.